From Religious Bubble to Interreligious Dialogue: A Personal Story of Transformation - Hulsman, Cornelis (Religions, 2024)
This paper argues that interreligious dialogue through study and friendships across the religious divide makes participants less susceptible to religious and cultural misinformation that is often used to maintain social bubbles, in which members draw clear boundaries between “us” and “them”. Differences between social groups can culminate in a struggle between good and evil that can escalate into tension and violence. Preventing tensions and conflicts requires respect for differences, willingness to engage in dialogue, and a sound understanding of what religion is and the historical processes that have determined its development, distinguishing between empirical facts and images to which believers adhere. Because the author is a Dutch sociologist turned journalist from a conservative Christian family involved in interreligious dialogue in the Netherlands, Israel, and Egypt, the literature review presents contemporary religious developments in all three countries. The literature review is flanked by the author’s personal narrative on the events that changed his views on truth and spirituality, making him more aware of the commonalities between peoples of different beliefs and leading him to a lifelong commitment to interreligious and intercultural dialogue.